Akhmet Zaki Validi Togan and the kazakh-turkish intellectuals in the national liberation movement of turkestan (Journal of history, 2020)
Memoirs of Zaki Validi Togan, eminent person of the national liberation movement of Turkestan became an important source for revision of the events which were taking place during this period. This historic figure took active part in the political processes happening in Turkestan in 1920-1923. Validi’s memoirs have been for the first time published in Turkey in 1963. In 1994-1996 the book of memoirs has been translated into Russian and published. The analysis of memoirs of Validi in the course of which comparison with memoirs and articles of M. Shokay and other politicians of Turkestan was carried out gives the chance to draw conclusions concerning extent of influence of the socio-political, spiritual and religious ideas which arose during an era of young Turkish revolution to social and political movement in Turkestan. In article the scientific value of these memoirs where the author not only is the witness of the taking place events, but their active participant is also considered. Key words: Central Asia, Turkey, Turkestan, Bukhara, ZakiValidi, national liberation movement, colonial power